Obstacles to Seniors’ Community Integration in Malaysia: A Qualitative Investigation from the Viewpoint of Occupational Therapists - Yau Y. Hui,; Nathan Vytialingam,; Sangeeta K. Singh, (Public Health, 2025)
Introduction Existing research has addressed the importance of community integration (CI) and its benefits of dwelling in a community but has yet to address the methods and efficiency of improving these activities among older people. Thus, it is vital to understand how healthcare workers can integrate the benefits of CI among older people, especially with the use of occupational therapists (OTs). The latter are actively working to improve ageing individuals mobility within the community. Objective This study aims to identify Malaysian OTs’ perspectives on CI’s and its implication on older people. Method Occupational therapist from different states of Malaysia participated in a semi-structured interview, through a virtual medium (Zoom Cloud Meetings). The interview guide encapsulated the theory of critical incident technique (CIT). Results Thematic content analysis, over fourteen participants from 13 states of Malaysia, provided insights into CI’s barriers for older people in Malaysia. The findings revealed that multifaceted factors from an individual, organisational and socio-environmental perspective limit older people’s active CI engagement. Conclusion South-East Asia hierarchal and collectivist culture play a significant role in influencing all factors of CI. OTs must understand and incorporate appropriate cultural norms during CI practice development for the older population in Malaysia.